THE EFFECT OF WATER CAPACITY ON THE ACTIVITY OF PD(II)-CU(II) CATALYST ANCHORED TO ACID-MODIFIED CLINOPTILOLITE IN THE REACTION OF LOW-TEMPERATURE CARBON MONOXIDE OXIDATION - T. L. Rakitskaya (Vìsnik Odesʹkogo Nacìonalʹnogo Unìversitetu: Hìmìâ, 2015)
The maximum activity of Pd(II)-Cu(II) catalyst anchored to acid modified clinoptilolite in the reaction of low-temperature carbon monoxide oxidation with air oxygen has been found at the water content in the range from 3.3 to 4.2 mmol/g.